Modified atmosphere and cold storage for postharvest conservation of ’Niagara Rosada’ table grape - Cia, Patrícia; Benato, Eliane Aparecida; Valentini, Silvia Regina de Toledo; Sanches, Juliana; Ponzo, Francine Scolfaro; Flôres, Daniela; Terra, Maurilo Monteiro (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the effect of the modified atmosphere, on the storage life of ’Niagara Rosada’ Table grape kept under refrigeration in two experiments. In the first one, grape clusters stored in different package materials were evaluated: corrugated cardboard boxes, polyethylene tereftalate (PET); 17-μm polyvinyl chloride (PVC); 25-μm low density linear polyethylene film (PELDB); and 50-μm PELDB. On a second assay, different packaging systems were evaluated: opened plastic bags; 25-μm low density polyethylene film (PEBD); 25-μm PEBD, with injection of gas mixture (21% O2/5% CO2), 25-μm PEBD (21% O2/10% CO2); 25-μm PEBD (21% O2/20% CO2). The grape clusters were stored at 1±1°C and 90 ± 5% relative humidity (RH) for 28 days, followed by a storage period at room conditions at 25 ± 2ºC and 80± 5% RH. Clusters were evaluated for weight loss, firmness, color of the berries, percentage of detached berries, total soluble solids (SST), titratable acidity (TA), SST/TA, and rot incidence. Polyethylene film of 50-μm, from the 14th day at 1°C, with an additional period of 3 days at 25°C, caused fruit fermentation. The 25-μm PELBD, with or without gas injection, and 17-μm PVC films reduce clusters weight loss, but do not reduce berry detaching and rot incidence .